A NUMERICAL APPROACH FOR THE STUDY OF HEAT GENERATION IN THE PRESENCE OF THERMAL BOUNDARY LAYER FOR A FLAT PLATE - Auwal, D. M.; Gafai, M. M.; Garba, A. A.; Shehu, Mustapha (FUDMA JOURNAL OF SCIENCES, 2023)
In this study, we investigate the laminar boundary layer flow in two dimensions, steadiness, and incompressibility around a moving vertical flat plate in a uniform free stream of fluid with a convective surface boundary condition. The similarity transformation technique has been applied to convert the governing nonlinear partial differential equation into two nonlinear ordinary differential equations. By combining the finite difference method with the shooting technique, the problem is solved numerically. We present a tabular and graphical representation of the variation in dimensionless temperature and fluid-solid interface characteristics for various values of the Prandtl number. As a special case of the problem, a comparison between the current result and the previously published result demonstrates a good agreement.